Prevalence, intensity and associated risk factors of Schistosoma mansoni infections among schoolchildren around Lake Tana, northwestern Ethiopia - Tamirat Hailegebriel; Endalkachew Nibret; Abaineh Munshea; Zena Ameha (Public Library of Science (PLoS), 2021)
Background Schistosomiasis is one of the widely distributed neglected tropical diseases. It is a serious public health problem in sub-Saharan Africa. The disease is highly prevalent and widely distributed in Ethiopia due to suitable environmental factors and human activities. The prevalence and infection intensity varied from locality to locality in the country. This study aimed to assess the prevalence and intensity of S. mansoni infection and associated risk factors among schoolchildren around Lake Tana. Methods A school-based cross-sectional study was conducted among 710 schoolchildren from February to April 2021 in eight selected primary schools around Lake Tana. A questionnaire was used to collect data on socio-demographic information and potential risk factors of S. mansoni infection. After collecting socio-demographic information, students were requested to bring about 2grams of stool specimens for parasitological examination. The collected stool samples were processed using a single Kato-Katz and Ritchie's concentration techniques. The data were analyzed using SPSS software version 23 and factors with a p-value < 0.05 were considered as statistically significant. Results The overall prevalence of S. mansoni was 34.9% (95% CI: 31.4-38.7) among schoolchildren in the study area. The eggs per gram (EPG) of stool ranged from 24 to 1659 with arithmetic and geometric mean values of 138.1 EPG and 85.1 EPG, respectively. The majority of S. mansoni infections (61.4%) were classified as low infection intensity. Among the different determinant factors being male (AOR = 1.74; 95%CI = 1.233-2.457; P-value = 0.002), bathing habits (AOR = 1.494; 95%CI = 1.013-2.199; P-value = 0.043) and students attending at Qunzela primary school (AOR = 10.545; 95%CI = 3.264-34.067; P-value = 0.001), Alabo primary school (AOR = 3.386; 95%CI = 1.084-10.572; P-value = 0.036) were significantly associated with S. mansoni infection. Conclusion This study revealed that more than one-third of schoolchildren were infected by S. mansoni in the study area. The majority of the infections were classified as low infection intensity. Being male, bathing habits and schools in which students attended were independent explanatory factors for S. mansoni infection. Therefore, integrated control strategies are needed to improve the health conditions of schoolchildren in the study area. Author summary We conducted a school-based cross-sectional study to assess the prevalence and intensity of Schistosoma mansoni infection and associated risk factors. Stool samples were collected from 681 schoolchildren and processed using Kato-Katz and Ritchie's concentration techniques. Among those students, 238 (34.9%) were infected with S. mansoni. Kato-Katz and Ritchie's concentration detect 220 (92.4%) and 165 (69.3%) of the total positive cases, respectively. Most of the S. mansoni infections were categorized as low infection intensity based on egg per gram of stool. Among the potential risk factors assessed; being male, bathing habits in open water and schools in which students attended were independent predictors for S. mansoni infection.